Novel Highly Energetic Pyrazoles: N‐Trinitromethyl‐Substituted Nitropyrazoles. Issue 9 (14th July 2015) - Dalinger, Igor L.; Vatsadze, Irina A.; Shkineva, Tatyana K.; Kormanov, Alexandr V.; Struchkova, Marina I.; Suponitsky, Kyrill Yu.; Bragin, Anatoly A.; Monogarov, Konstantin A.; Sinditskii, Valery P.; Sheremetev, Aleksei B.
Abstract A new family of energetic compounds, nitropyrazoles bearing a trinitromethyl moiety at the nitrogen atom of the heterocycle, was designed. The desirable high‐energy dense oxidizers 3, 4‐dinitro‐ and 3, 5‐dinitro‐1‐(trinitromethyl)pyrazoles were synthesized in good yields by destructive nitration of the corresponding 1‐acetonylpyrazoles. All of the prepared compounds were fully characterized by multinuclear NMR and IR spectroscopy, as well as by elemental analysis. Single‐crystal X‐ray diffraction studies show remarkably high density. Impact sensitivity tests and thermal stability measurements were also performed. All of the pyrazoles possess positive calculated heats of formation and exhibit promising energetic performance that is the range of 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine and pentaerythritol tetranitrate. The new pyrazoles exhibit positive oxygen balance and are promising candidates for new environmentally benign energetic materials.